The Role of Soft Skills in Supporting Journalist Performance in Disaster Prone Area - Zainul Hidayat; Yessy Anggraeni; Mokhamad Taufik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to determine conceptually-theoretically the soft skills and performance of individuals who pursue certain professions, especially journalists who work in Disaster-Prone Areas. The method used in this study is the library research method, or it can also be called the literature review method, which is a type of study conducted by examining relevant related literature. Based on the results of data analysis, it can be concluded that soft skills are relatively closely related to performance even in situations and conditions that are not normal. An objective news presentation certainly requires special skills or abilities for journalists. Then there are some basic skills or abilities that journalists need to have. Some of these abilities that journalists need to have, namely writing properly and correctly, establishing communication with sources and skills in using information technology tools. It is not enough for journalists with assignment locations in Disaster Prone Areas to have basic skills. Need additional soft skills according to the situation and conditions. There is a fundamental difference between the duties of journalists in normal situations and conditions with disasters. Both in terms of sources and the accuracy of the information and news presented.